Archaeal biofilm formation. Issue 11 (November 2018) - Wolferen, Marleen; Orell, Alvaro; Albers, Sonja-Verena
Abstract Biofilms are structured and organized communities of microorganisms that represent one of the most successful forms of life on Earth. Bacterial biofilms have been studied in great detail, and many molecular details are known about the processes that govern bacterial biofilm formation, however, archaea are ubiquitous in almost all habitats on Earth and can also form biofilms. In recent years, insights have been gained into the development of archaeal biofilms, how archaea communicate to form biofilms and how the switch from a free-living lifestyle to a sessile lifestyle is regulated. In this Review, we explore the different stages of archaeal biofilm development and highlight similarities and differences between archaea and bacteria on a molecular level. We also consider the role of archaeal biofilms in industry and their use in different industrial processes. Archaea have been found in biofilms in a variety of habitats. In this Review, Albers and colleagues explore the different stages of archaeal biofilm development and highlight the similarities and differences between archaea and bacteria. They also consider their role in different industrial processes.